1966
DOI: 10.1039/j39660000078
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of diazomethane with 2,2′-azopyridines

Abstract: It is shown by spectral evidence and independent synthesis that diazomethane and 2,2'-azopyridine yield N-formyl-2,2'-hydrazopyridine rather than a diazetidine, as previously suggested.COLOWA and RISALITI reported that diazomethane and 2,2'-azopyridine gave a crystalline product, m. p. 143-144", to which they assigned the diazetidine structure (I). This remarkable reaction seemed worthy of further investigation. The reaction as described did indeed yield a crystalline compound, m. p. 140--141", but elemental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…These structures, therefore, do make a significant contribution to the overall structure. This is consistent with the enhanced resonance effects associated with 1r-electron donors and their stabilizing interactions Oi" (Essery & Schofield, 1963;Katritzky & Simmons, 1960;Becker, Miles & Bradley, 1965). The geometryoptimized 1NDO calculations have shown that the quinoid resonance hydbrids (la'), (lc') and (2') do make a defnite contribution to the overall structure of the compounds (Barbieri, Benassie, Grandi, Pagnoni & Taddei, 1979).…”
supporting
confidence: 53%
“…These structures, therefore, do make a significant contribution to the overall structure. This is consistent with the enhanced resonance effects associated with 1r-electron donors and their stabilizing interactions Oi" (Essery & Schofield, 1963;Katritzky & Simmons, 1960;Becker, Miles & Bradley, 1965). The geometryoptimized 1NDO calculations have shown that the quinoid resonance hydbrids (la'), (lc') and (2') do make a defnite contribution to the overall structure of the compounds (Barbieri, Benassie, Grandi, Pagnoni & Taddei, 1979).…”
supporting
confidence: 53%
“…Comparison of the ρ-values for the protonation of concave phenylethynyl pyridines 3 with the ρ-values for the protonation of 4-substituted pyridines 6, 4-aryl pyridines 7, 4-styryl pyridines 8, 4-phenylethynyl pyridines 9, and concave pyridines 1bϪd. The ρ values for 6, [26] 7, [27] 8, [28] and 9 [28] were taken from the literature, the ρ value for 1 [29] was determined by use of σ ϩ [30,31] With the UV spectra for protonated and unprotonated concave pyridines 3 now known, additional experiments in the presence of acidic molecules could then be carried out to determine whether compounds 3 could be used to study the formation of hydrogen bonds. When the UV spectra of the unprotonated concave pyridines 3 and 5 were compared in different solvents (e.g., dichloromethane and methanol), solvatochromism was observed for the concave pyridines 3.…”
Section: Resultsmentioning
confidence: 99%
“…General Remarks: The following chemicals were obtained commercially and were used without further purification: bis(triphenylphosphanyl)palladium() dichloride (Fluka), copper() iodide (Fluka), phenylacetylene (2a, Janssen). 29-Iodo-1,14,33-triaza-17,20,23-trioxatricyclo[12.11.7.1 27,31 ]tritriaconta-27(33),28,30triene-2,13-dione (1a) [17] and dimethyl 4-iodopyridine-2,6-dicarboxylate (4) [17] were prepared by literature procedures. The terminal alkynes 2b, [19] 2c, [20] 2d, [20] 2e, [21] and 2f [22] were prepared from the iodoarenes by Sonogashira coupling according to the cited literature.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, little effort has been devoted to studying the various parameters in relation to each other. Katritzky et al [10] had undertaken a comprehensives study of the effectiveness of the better known solvent polarity parameters over a wide variety of solvent-dependent phenomena (spectroscopic, kinetic and equilibrium) with the aim of determining the most successful measure of solvent "polarity". Since it transpires that no single parameter can deal effectively with all the types of phenomenon which vary with solvent.…”
Section: Uv Spectrophotometric Studiesmentioning
confidence: 99%